2018
DOI: 10.3892/mmr.2018.8905
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibition of JAK1,2/Stat3‑PD‑L1 signaling pathway suppresses the immune escape of castration‑resistant prostate cancer to NK cells in hypoxia

Abstract: Castration-resistant prostate cancer (CRPC) is difficult to treat in current clinical practice. Hypoxia is an important feature of the CRPC microenvironment and is closely associated with the progress of CRPC invasion. However, no research has been performed on the immune escape of CRPC from NK cells. The present study focused on this subject. Firstly, when the CRPC cell lines C4-2 and CWR22Rv1 were induced by hypoxia, the expression of the UL16 binding protein (ULBP) ligand family of natural killer (NK) group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 52 publications
1
37
0
Order By: Relevance
“…As for the IL6-JAK-STAT3 signaling, studies showed it involved in tumor growth, metastasis, and the immune escaping. [23][24][25][26][27] Therefore, it may be a reason for unfavorable prognosis in low-purity group. Both IL2-STAT5 signaling and IL6-JAK-STAT3 signaling may become potential immunotherapeutic targets for low-purity gastric tumors.…”
Section: Discussionmentioning
confidence: 99%
“…As for the IL6-JAK-STAT3 signaling, studies showed it involved in tumor growth, metastasis, and the immune escaping. [23][24][25][26][27] Therefore, it may be a reason for unfavorable prognosis in low-purity group. Both IL2-STAT5 signaling and IL6-JAK-STAT3 signaling may become potential immunotherapeutic targets for low-purity gastric tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Castration-resistant prostate cancer (CRPC) cells increased the expression of PD-L1 which participated in tumor immune evasion under hypoxic conditions. Silencing STAT3 signaling can reverse the level of PD-L1 and enhance the susceptibility of CRPC cells to NK cell immunity [ 155 ].…”
Section: Stat3 Target Genes Impact Chemoresistance and Radioresistmentioning
confidence: 99%
“…Cytotoxicity assays. CytoTox 96 ® non-radioactive cytotoxicity assay (Promega Corporation) was used for the detection of SW480 cell killing by NK-92 cells according to the manufacturer's protocol as a previous report (15). SW480 cells were first washed with PBS, re-suspended in fresh NK-92 culture medium (fully supplemented as previously described) and seeded into 96-well plates (density, 5x10 3 cells/well).…”
Section: Methodsmentioning
confidence: 99%